Serum Lead Level and Polyneuropathy among Bangladeshi Patients (Bangladesh Journal of Neuroscience, 2015)
Background: Heavy metals may produce various symptoms among the exposed, of which polyneuropathy is a matter of real concern. Our aim was to determine the pattern and association between polyneuropathy and blood lead level.Methods: This case control study was done in the department of Neurology, Bangabandhu Sheikh Mujib Medical University, Dhaka in collaboration with Bangladesh Atomic Energy Centre from July 2001 to June 2002. The lead concentration in the blood was detected by Xray fluorescence (XRF) technique. Nerve conduction study and CSF examination were done among the cases.Result: Data were collected from 92 respondents, of whom cases and controls were equal in number with a male to female ratio of 8.17:1. Mean age of the cases and controls were 30.87 +14.53 years and 30.91+ 12.03 years respectively. Among the cases, 55% had sub acute type of polyneuropathy, followed by acute and chronic type of polyneuropathy among 30% and 15% respondants respectively. The mean CSF protein level was 112.00 + 65.04 gm/L. The mean CSF protein was higher in acute polyneuropathy than in subacute and chronic cases (p